Breastfeeding in Nigeria: a systematic review - Adewuyi, Emmanuel O.; Adefemi, Kazeem (International Journal Of Community Medicine And Public Health, 2017)
Breastfeeding confers numerous benefits on babies and mothers. Early initiation, ‘exclusive breastfeeding’ and breastfeeding for at least two years post-delivery are the recommended practices. This study aims to examine the trends of breastfeeding practice in Nigeria by reviewing available published studies. The online databases of PubMed, Science Direct and the Web of Knowledge were searched using relevant terms. Studies identified were screened for eligibility and those that met the inclusion criteria were included in this review. Graphs and regression equations were generated using Microsoft Excel® to illustrate the duration of and trends in, breastfeeding practices in Nigeria. This review adopts the WHO standard definitions for breastfeeding categories. A total of 24 studies met the inclusion criteria but only two of these adopted the standard WHO breastfeeding categories in estimating the rates of breastfeeding. The regression equations and graphs generated show a declining trend in the rates of ‘exclusive breastfeeding’ and an increasing trend in the mean duration of breastfeeding. The rate of ‘any breastfeeding’ was high. Breastfeeding duration varies across Nigeria, a possible reflection of differences in sociocultural practices. Various reasons were cited for discontinuation of breastfeeding, the commonest of these were maternal health problems and the demands of work.Breastfeeding is commonly practiced in Nigeria. However, the rate of ‘exclusive breastfeeding’ is low and declining. It is recommended that future studies on breastfeeding in Nigeria adopt the standard WHO definitions.